Beauchamp Hall [compact disc, unabridged] - Steel, Danielle (Recorded Books, LLC, 2018)
Beauchamp Hall is perfect for the holidays, a delightful novel about a young American woman who finds love and fulfillment in the course of her involvement with a Downton Abbey-style TV show in England.